(Dis)Abling church spaces: Walking the talk of inclusivity in Zimbabwe - Tagwirei, Kimion (HTS teologiese studies, 2025)
Since time immemorial, the Church has had much to say about people living with disabilities in and beyond its walls. Commendably, in Zimbabwe, the Church has established and supported schools for people with hearing, visual, physical and psychological impairments. A lot has been said and published about the Church and disabilities, especially concerning church-driven empowerment and inclusion. However, in reality, and hypocritically, infrastructural, liturgical, leadership, ministerial and related spaces of the Church have remained inaccessible and exclusive. Transforming Church spaces is crucial to ensure comprehensive inclusivity in Zimbabwe. In view of unwelcoming ecclesial spaces in the Zimbabwean context, this article applied Osmer’s practical theological methodology of observing, interpreting, assessing and strategic problem-solving to review the Church’s talk and deeds of inclusivity. It argued that exclusivity is self-defeating, because it contradicts the inclusive missio dei, missio ecclesiae, and neglects the vulnerability of everyone to disabilities. While appreciating past and present utterances and contributions of the Church to achieve inclusion, this article contends that real inclusivity will be realised only when the Church lives out its inclusionary words by realising accessibility for everyone, regardless of impairments and diversities.Contribution: Reconciling the talk and walk of the Church on (dis)abilities by reviewing church spaces makes a crucial contribution towards transforming African ecclesiologies, theology of disability, missiology and development.